Mammal Review - Mammal Review (Wiley, 2026)
Mammal Review is a leading journal in mammalogy that publishes high-quality review articles covering all aspects of mammalian biology and ecology. Its scope includes conservation, behavior, population dynamics, and interactions between mammals and their environments. The journal aims to support international research and contribute to the conservation of mammal species, including efforts to prevent biodiversity loss and improve understanding of ecological processes affecting mammals worldwide.
FI 1.05
Q1
Keywords: Life Sciences; Animal Science & Zoology; Ciencia animal; Zoología; Acuerdos transformativos; Transformative agreements; Mastozoología; Ecología del comportamiento; Biogeografía; Conservación